The Effectiveness of Emergency Drill to Prepare Crew to Face Abandoned Ships on MT. Pagerungan - Daffanda Yoda Wibisono; Elise Dwi Lestari; Elly Kusumawati; Upik Widyaningsih (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Safety of life at sea is a paramount operational priority that heavily relies on crew preparedness in managing maritime emergencies. This study evaluates the effectiveness of abandon ship drills in improving crew readiness on the commercial tanker MT. Pagerungan. Using a qualitative case-study design, data were collected over a 12-month period through direct participant observations, structured interviews with six key personnel, and documentary analysis. Effectiveness was measured using specific operational indicators: alarm response time, correct usage of life-saving appliances (LSAs), compliance with muster list duties, and communication efficiency. The results indicate a significant gap between administrative compliance and practical readiness. Drills were conducted only four times annually, violating the monthly requirement stipulated by the Safety of Life at Sea (SOLAS) Convention. Observations revealed critical deficiencies, including the inability of junior and catering crew members to correctly don lifejackets and a lack of role awareness among specific deck ratings. Furthermore, commercial pressures and a tendency to view drills as bureaucratic formalities hindered the development of a robust safety culture. The study concludes that while incremental improvements were observed across repeated drills, overall effectiveness remains structurally fragile. Recommendations include the rigorous implementation of monthly drills, integration of pre-drill toolbox meetings, station-specific compliance checklists, and documented competency assessments to bridge the gap between regulatory mandates and actual emergency preparedness